Nasilje v družinah v okoljih, kjer "vsak vsakega pozna" - Knežević Hočevar, Duška (Socialno delo, 2016)
The article discusses some findings of the qualitative research "Recognizing and treating victims of domestic violence in health care settings", which addresses the understandings of domestic violence in rural environments. Research was conducted in 2015 with both health care practitioners (14) and other professionals (16) in urban and rural settings all over Slovenia, who are dealing with domestic violence in their work. The results imply certain aspects of rurality, which contextualize general discourses and practices of domestic violence in both victims and perpetrators and various practitioners who work with them. Living and working in settings where "everybody knows each other" determine unreliable reporting on domestic violence prevalence, its high tolerance and poor recognition in practitioners of supporting institutions who as a rule know both - the victim and the perpetrator of domestic violence. Few, scattered and unrelated social and health care systems hinder victims to leave their violent relationship. The solution remains a coordinated community response of all actors involved in treating domestic violence.
Keywords: family violence; nasilje v družini; podeželje; rural area; rural areas; Slovenia; Slovenija; social problems; družbeni problemi; social work; socialno delo